HAK MENDAHULUI UPAH PEKERJA DALAM PERKARA KEPAILITAN (Analisis Putusan MK No. 18/PUU-VI/2008 Jo No. 67/PUU-XI/2013) - Muhamad Abas (BUANA ILMU, 2018)
ABSTRAK Hak mendahului (hak preferen) upah pekerja dalam perkara kepailitan perusahaan sebaiknya dilakukan dengan penerapan asas kepastian hukum dan keadilan serta manfaat, hal ini dimaksudkan agar efektivitas penerapan dan pelaksanaan dari putusan Mahkamah Konstitusi(MK) No. 67/PUU-XI/2013 yang menyatakan upah pekerja harus didahulukan dapat terlaksana dengan baik. Terdapat benturan kepentingan antara kreditor saat terjadi kepailitan dan mudahnya syarat kepailitan. Putusan MK pertama lebih mengedepankan asas kepastian hukum daripada asas keadilan dan sependapat dengan pemerintah lebih melindungi investor daripada pekerja. MK menolak permohonan para Pemohon. Putusan MK kedua Majelis hakim bersifat responsif dalam memutus permohonan, menjunjung tinggi nilai keadilan berdasarkan pada nilai-nilai kemanusiaan dengan mempertimbangkan subjek hukum, objek hukum dan risiko yang timbul akibat kepilitan. MK menerima permohonan para Pemohon sebagian. Inkonsistensi penegakkan hukum bertentangan dengan konsep negara kesejahteraan dimana tugas negara memikul tanggungjawab mewujudkan keadilan sosial, kesejahteraan umum dan sebesar-besarnya untuk kemakmuran rakyat. Keadilan terhadap kedudukan pekerja dengan kreditor lainnya dapat terwujud apabila masyarakat menganut prinsip keadilan yang sama atau mempunyai pokok pikiran yang sama dalam perkara kepailitan. Kata Kunci : â€œ Hak Preferen, Upah Pekerja, Kepailitanâ€. ABSTRACT Preemptive rights (preferential rights) of workers' wages in the case of corporate bankruptcy should be carried out with the application of the principle of legal certainty and justice and benefits, this is intended so that the effectiveness of the implementation and implementation of the Constitutional Court decision No. 67 / PUU-XI / 2013 which states that workers' wages must take precedence can be carried out well. There is a conflict of interest between creditors when bankruptcy occurs and easy bankruptcy requirements. The first decision of the Constitutional Court to prioritize the principle of legal certainty over the principle of justice and agree with the government to protect investors more than workers. The Court rejected the Petitioners' petition. The second Constitutional Court verdict The panel of judges is responsive in deciding the petition, upholding the value of justice based on human values by considering legal subjects, legal objects and risks arising from constriction. The Court accepted the request of the Petitioners in part. The inconsistency in enforcing the law contradicts the concept of a welfare state where the duty of the state to assume responsibility is to realize social justice, public welfare and as much as possible for the prosperity of the people. Justice towards the position of workers with other creditors can be realized if the community adheres to the same principle of justice or has the same subject matter in bankruptcy cases. Keywords: "Preferential Rights, Workers' Wages, Bankruptcy".